Trypanosoma cruzi discrete typing units in Chagas disease patients from endemic and non-endemic regions of Argentina - Cura, Carolina Inés (2012)
Fil: Cura, C I. Laboratorio de Biología Molecular de la Enfermedad de Chagas, Instituto de Ingeniería Genética y Biología Molecular (INGEBI-CONICET), Vuelta de Obligado 2490, 2do piso, 1428, Ciudad de Buenos Aires; Argentina.